Changes in lower-limb neuromuscular performance from pre-season to the end of the early competitive period in elite male professional soccer players - Ferrari, R.; da Silva, W. B.; de Oliveira Carpes, L.; Lazzari, C.; Silveira, A. D. (Frontiers in Sports and Active Living, 2026)
Background: The increasing compression of the pre-season period due to congested calendars may induce significant neuromuscular fatigue, potentially compromising player readiness for competition.